Streptococcal toxic shock syndrome in a returning traveller. Issue 6 (2nd November 2019) - Note, Stéphanie; Soentjens, Patrick; Van Laer, Marie; Meert, Philippe; Vanbrabant, Peter
ABSTRACT: Background:  A patient presenting with fever and purpura after a stay in the tropics tempts a physician to make a differential diagnosis mainly focusing on imported diseases. Although the importance of considering a tropical disease is obvious, the fact that cosmopolitan infections account for one third of the cases in a febrile returning traveler must not be overseen. Toxic Shock Syndrome is amongst the most notorious diseases due to the high mortality when inappropriately managed and the association with necrotizing fasciitis. Methods  : We present a 60-year old female with fever, shock syndrome and progressive appearance of painful purpura on the lower legs after a 2-week holiday in Zanzibar. Results  : The patient was diagnosed with Streptococcal Toxic Shock Syndrome. Treatment focusing on aggressive fluid resuscitation, prompt administration of antibiotics (ceftriaxon, doxycycline and one dose of amikacin) and adjunctive treatment by clindamycin and immunoglobulin was initiated. She was also immediately taken into surgery for a bilateral fasciotomy and surgical exploration of the lower legs. Histology appeared compatible with purpura fulminans, thereby excluding necrotizing fasciitis. No source of infection could be identified.  Conclusion : Toxic Shock Syndrome remains a challenging diagnosis and even more in a returning traveler with an extensive differential diagnosis containing both tropical and cosmopolitan diseases. Cornerstones for the treatment of Streptococcal Toxic Shock Syndrome are abrupt administration of antimicrobial therapy comprising beta-lactam antibiotics and clindamycin and surgical exploration to apply source control when indicated.